2013
DOI: 10.1001/jamaoto.2013.3969
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a Predictor of Morbidity and Mortality in Inpatient Head and Neck Surgery

Abstract: The mFI is significantly associated with morbidity and mortality in this retrospective survey. Additional study with prospective analysis and external validation is needed. The mFI may provide an improved understanding of preoperative risk, which would facilitate perioperative optimization, risk stratification, and counseling related to outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
256
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(270 citation statements)
references
References 16 publications
10
256
2
2
Order By: Relevance
“…Similarly, an ASA score of 4 or more for open (vs. laparoscopic) colectomy was also predictive of class IV and V complications, although the ORs were less (Obeid et al, 2012). These results were confirmed by Adams et al (2013) that showed that the risk of grade IV complications increased from 1.2% to 26.2% for open or laparoscopic colectomy, and the overall risk of any complication increased from 9.5% to 40.5%.…”
Section: Grade IIImentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly, an ASA score of 4 or more for open (vs. laparoscopic) colectomy was also predictive of class IV and V complications, although the ORs were less (Obeid et al, 2012). These results were confirmed by Adams et al (2013) that showed that the risk of grade IV complications increased from 1.2% to 26.2% for open or laparoscopic colectomy, and the overall risk of any complication increased from 9.5% to 40.5%.…”
Section: Grade IIImentioning
confidence: 70%
“…A large population study (the National Surgical Quality Improvement Program; NSQIP) demonstrated that pre-operative frailty state is a strong predictor of cardiac arrest and death, and showed that it's a better indicator of post-operative mortality compared to the scoring system of the American Society of Anesthesiologists' (ASA) (Larsen & Rubinfeld, 2012). Frailty, assessed using a modified frailty index (mFI), was also associated with a higher mortality-risk in patients who underwent otolaryngology surgery: robust individuals had a mortality rate of around 0.2% whereas those with a high frailty score had a much higher value at around 12% (Adams et al, 2013) Among the different physical frailty components included in the Fried's scale (Fried et al, 2001), slow gait speed was an independent predictor of mortality among patients scheduled for cardiac surgery (Afilalo et al, 2010). In another study, frailty was a factor associated with poorer 90-day and 1-year overall survival (OR = 10.4 and 8.4 respectively) in the oldest elderly-patient group (aged 80 and over) who underwent elective surgery for colon cancer (Neuman et al, 2013).…”
Section: The Relationship Between Frailty Syndrome and Postoperative mentioning
confidence: 99%
“…In the United States, the population of adults aged 65 and older is expected to reach 80 million during the years 2010-2040. 10 According to Social Development Canada, approximately one quarter of the population in Canada will be over the age of 65 by the year 2041. Increasing age has a well-defined correlation with frailty status, but aging alone is not necessarily synonymous with frailty.…”
Section: What Is Frailty?mentioning
confidence: 99%
“…In the modified system, hospital stay was eliminated as a criterion, the weight of life-threatening complications involving organ failure was increased, and disability requiring follow-up was acknowledged with the suffix 'd'. Since 2004, the Clavien-Dindo system has been widely used in surgical studies, including large cohorts and randomised controlled trials [28,29].…”
Section: Complicationsmentioning
confidence: 99%